The Impact of Constitutional Court Decision No. 105/PUU-XXII/2024 on Restrictions on Defamation Lawsuits on the Public's Right to Oversee Power: An Institutional and Constitutional Analysis - Muhamad Irwan; Rizky Perdana Bayu Putra; Tuti Handayani; Elmi Sasmitaningtyas; Milka Kumala (Universitas Kristen Cipta Wacana, 2025)
This article examines the impact of Constitutional Court Decision No. 105/PUU-XXII/2024, which restricted criminal defamation claims by institutions under the Electronic Information and Transaction Law. The ruling asserts that only individual persons—not state bodies, corporations, professions, or institutional entities—may file criminal defamation reports. Employing a normative legal method with statutory and constitutional approaches, the study analyses the decision’s implications for public oversight over governmental power, democratic deliberation, and institutional accountability. This paper argues that the decision strengthens citizens’ freedom of expression and the informal mechanism of checks and balances, while also reducing the potential misuse of criminal defamation provisions to silence criticism. However, the effectiveness of the ruling depends on judicial interpretation, harmonisation with other legal frameworks, and the institutional internalisation of democratic norms. The research concludes that although the decision contributes to the protection of civil liberties, a more systematic enforcement strategy, judicial guidelines, and legal reform are required to prevent retaliatory litigation through non-criminal avenues. Furthermore, this study contributes to constitutional scholarship by positioning the decision as a landmark shift from state-centred reputational protection towards citizen-centred constitutional guarantees. It highlights the need for a coherent legal architecture that safeguards critical expression as an essential component of democratic control over power. By mapping doctrinal consequences and practical enforcement gaps, this article offers a framework for evaluating future court rulings and policy reforms related to defamation, digital rights, and state accountability in Indonesia. Thus, the decision not only redefines the boundaries of criminal defamation but also provides momentum for strengthening constitutional democracy through legal culture transformation, legislative harmonisation, and strategic judicial oversight.